The Effect of Rice Straw Mulch and Plus Organic Fertilizer Residue on The Growth of Glutinous Corn (Zea mays ceratina Kulesh) - Hadi Riyandi; La Ode Afa; La Ode Safuan; La Karimuna; La Ode Sabaruddin (Universitas Sembilanbelas November Kolaka, 2022)
This study aimed to determine the effect of rice straw mulch and plus organic fertilizer residue on the growth of glutinous corn. This study was conducted from May to July, 2022 at the Field Laboratory, Faculty of Agriculture, Halu Oleo University, Kendari, Southeast Sulawesi. This study used a randomized block design with split-plot design treatments. Main plots were residue of rice straw mulch (M): without residue of rice straw mulch (M0), 4 t ha-1 residue of rice straw mulch (M1), and 8 t ha-1 residue of rice straw mulch (M2). Main subplots were residue of plus organic fertilizer (P): without residue of plus organic fertilizer (P0), 2.5 t ha-1 residue of plus organic fertilizer (P1), 5 t ha-1 residue of plus organic fertilizer (P2), and 7.5 t ha-1 residue of plus organic fertilizer (P3). Each experimental unit was repeated three times. Measured variables were plant height, number of leaves, leaf area, , plant fresh weight, plant dry weight, and flowering age. The data were analyzed using ANOVA, if the analysis result was significant (Fhit Ftab), then analyzed further using DMRT on α=0.05. The research results showed a single effect in 8 t ha-1 residue of rice straw mulch (M2) or 7.5 t ha-1 residue of plus organic fertilizer (P3) by producing the highest growth of glutinous corn